Intensity of development of somatic diseases of children's population in Kizlyar and Khasavyurt and cancer incidence - F. I. Osmanova; I. N. Osmanov; T. F. Kosyreva (Эндодонтия Today)
Aim. Study of the development of somatic and oncological diseases and the state of the dentoalveolar system as an indicator of somatic health on the example of the city of Kizlyar (a city of ecological trouble) and the city of Khasavyurt (ecological well-being).Materials and methods. To determine the health status of children and their mothers, a survey was conducted of 1015 children and (or) their parents (three age groups of the study), of which 528 were girls and 487 were boys, and for comparison, 542 children aged 2-17 years in the city of Khasavyurt (ecological well-being) northern zone of Dagestan. Patient selection criteria: 1) identical area of residence (Kizlyar, Khasavyurt); 2) children of preschool age from 2-6 years (1, 2, 3 health groups in the absence of somatic diseases in sub- and decompensated forms), 4 health groups with chronic somatic diseases and congenital malformations; 3) Children at the age of the period of changeable occlusion from 7 to 13 years old, 1-4 health groups; 4) Children aged 14 to 17 years of permanent occlusion, 1-4 health groups.Results. According to a study of schoolchildren aged 7 to 17 years in the city of Kizlyar, 47.1% of children with habitual mouth breathing or mixed breathing. Infantile type of swallowing in children was found in 23.8% of cases. Violation of posture in children was observed in 29% of cases, while in children from the city of Khasavyurt, this type of violation was observed only in 10.5% of cases. The main localizations of malignant neoplasms in the male population are the respiratory organs, stomach, skin, bladder, lip; in the structure of oncological morbidity in the female population, the largest number of patients with neoplasms of the mammary gland, skin, lymphatic and hematopoietic tissue, cervix, and stomach.In the population (period of permanent occlusion), there was a significant decrease in tumors from 0.8% to 0.4% out of 1000 examined, the endocrine system from 0.5% to 0.4%, blood diseases from 0.2% to 0.1%.Conclusions. The results obtained confirm the presence and development of somatic and oncological diseases from unfavorable factors in the region of residence. All indicators for the city of Khasavyurt (ecological well-being) 2 times lower than the data of the city of Kizlyar (city of ecological trouble).